PENGARUH TERAPI SENAM LIEN TIEN KUNG TERHADAP PENURUNAN KADAR ASAM URAT PADA LANSIA - Christina, Elvrinica; A. Yullius Martha (LPPM STIKes Mitra Adiguna, 2025)
Gout or Gouty Arthritis is a disease with sudden and repeated attacks on the joints, characterized by the emergence of uric acid in the area caused by monosodium crystal deposits (inflammation) in the joints which collect as a result of high levels of uric acid in the blood. According to the World Health Organization (WHO), the incidence of gout in the elderly has increased by 355 million people. Objective To find out the technique of lien tien kung exercises to reduce uric acid levels in the elderly in the social institution for the elderly in our hope in Palembang in 2023. Method: The method used is pre-experimental research (Pre Experimental designs) with a One Group Pretest Posttest approach. The sample used was 20 respondents. Uric acid levels were measured using the Numeric Rating Scale (NRS) and observation sheet. Results: Based on the non-parametric statistical test (Wilcoxon), the calculated value for administering the Lien Tien Kung exercise was ? = 0.000 or (p value = 0.000 < 0.05). There is a significant difference based on the average uric acid level in the elderly before administering the lien tien kung exercise technique is 2.80 and the average uric acid level in the elderly after administering the lien tien kung exercise technique is 2.05. Conclusion: There is significance in administering the lien tien kung exercise technique to reduce uric acid levels. Providing the lien tien kung exercise technique is effective in reducing uric acid levels. Suggestion: It is hoped that future researchers can extend the administration time and can also look for other alternatives and then use different research methods.